G355(P) Healthy london partnership's child death overview panel (cdop) transformation programme: maximising learning from child death reviews across london. (May 2019) - Cheung, R; O'Sullivan, D; Parr, T; Devitt, D
Abstract : A three-year programme began in 2016 to support the London Child Death Overview Panel (CDOP) system to meet the significant transformational challenges they face. The London CDOP system accounts for 28 of 90 CDOPs in England. The publication of the National review of statutory guidance on Child Death Reviews (as part of the Children and Social Work Act (CSWA) gave an added impetus to transform the way in which these 28 CDOPs worked together to review deaths of children across the city. A baseline system survey revealed widespread variation in processes, resources and outcomes for the child death review process. Flowing from the survey and stakeholder engagement events, we supported the London CDOPs to align their practice via a series of workshops, generation of resources to enable London to respond to requirements of CSWA and new Statutory guidance. Year 1 outputs have included: Themed workshops addressing stakeholder priorities including Asthma and Neonatal Deaths, consanguinity, SUDI, Suicide Prevention and working relationships with Coroners Development of Pan London resources including review checklists for the above conditions, and resources for CDOPs to tackle bereavement support and suicide prevention – to support the delivery of a minimum standard of practice Pan London system level relationships including Coronial, Ambulance and Pathology systems and creation of agreed child death pathways across all providers within a coronial jurisdiction. Year two was geared towards transitioning to the new statutory Child Death Review standards. We worked with CDOPs in terms of their changing role, and how to increase their footprint in order to set up new governance structures. We also worked increasingly with healthcare providers to prepare them for their new role delivering the Child Death Review Meeting. We also obtained pump priming funding to deliver an electronic case management tool (eCDOPs) across all London CDOPs, as an enabler to align processes, release efficiencies to facilitate transition to the new system. Year three will continue to deliver system transformation support, but will also focus on the creation of an e-learning programme to support CDOP staff training across London, with a modular approach to allow tailoring of the course bespoke to learner needs, depending on their professional roles and requirements.